PEMBINAAN DAN PELATIHAN DALAM PENGEMBANGAN WIRAUSAHA PROGRAM KEGIATAN WIRAUSAHA MUDA SUMENEP (WMS) UNTUK MENGEMBANGKAN KEWIRAUSAHAAN: Bahasa Indonesia - Mohammad Imam Sufiyanto; Shalehoddin (CV ODIS, 2021)
The covid-19 pandemic hit the economy in the micro business sector, so there needs to be a role from the government, especially from the local government, the purpose of this study is to find out the development of entrepreneurship by developing new types of businesses or new products. The object of research is several types of micro businesses that can survive the current pandemic, in the microeconomic sector. The research method is descriptive qualitative, which can be done through three inflow of activities, namely: data reduction, data presentation, and drawing conclusions/verification. The result of this research is the development of new businesses both in terms of product design and type of business. The conclusion is that there is a business incubator to be able to develop a new entrepreneurial spirit and reduce entrepreneurship for young entrepreneurs in Sumenep Regency.